1993
DOI: 10.1080/09553009314552151
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotection of DNA by a DNA-binding Protein: MC1 Chromosomal Protein from the ArchaebacteriumMethanosarcinasp.CHTI55

Abstract: The archaebacterial chromosomal protein MC1 binds tightly and unspecifically to DNA; binding protects DNA against radiolysis by fast neutrons. At low covering of pBR322 plasmid DNA, one bound protein protects some 50 attack sites (phosphate-sugar moieties) against both single (ssb) and double strand breaks (dsb). At high covering of plasmid, protection against dsb becomes almost complete, although about half of the attack sites remain accessible to ssb. DNA restriction fragments were used to investigate the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Structural``histone-like'' DNA-binding proteins isolated from Archaea could play an important role in protecting DNA against denaturation and degradation (Searcy, 1986;Chartier et al, 1989;Imbert et al, 1990;Sandman et al, 1990;Musgrave et al, 1991;Agha-Amiri & Klein, 1993;Isabelle et al, 1993). The protein Sso7d from the hyperthermophilic archaeon Sulfolobus solfataricus belongs to a family of small (about 7 kDa), basic, abundant DNAbinding proteins found in Sulfolobales (Kimura et al, 1984;Choli et al, 1988a;Reddy & Suryanarayana, 1989); it shares about 90% sequence identity with the Sac7d/e family from Sulfolobus acidocaldarius (Choli et al, 1988b;Green et al, 1983;McAfee et al, 1995), but lacks obvious sequence similarity to any other known protein.…”
Section: Introductionmentioning
confidence: 99%
“…Structural``histone-like'' DNA-binding proteins isolated from Archaea could play an important role in protecting DNA against denaturation and degradation (Searcy, 1986;Chartier et al, 1989;Imbert et al, 1990;Sandman et al, 1990;Musgrave et al, 1991;Agha-Amiri & Klein, 1993;Isabelle et al, 1993). The protein Sso7d from the hyperthermophilic archaeon Sulfolobus solfataricus belongs to a family of small (about 7 kDa), basic, abundant DNAbinding proteins found in Sulfolobales (Kimura et al, 1984;Choli et al, 1988a;Reddy & Suryanarayana, 1989); it shares about 90% sequence identity with the Sac7d/e family from Sulfolobus acidocaldarius (Choli et al, 1988b;Green et al, 1983;McAfee et al, 1995), but lacks obvious sequence similarity to any other known protein.…”
Section: Introductionmentioning
confidence: 99%
“…Thermophilic members of the Archaea have histone proteins (24) known to give partial protection of plasmid DNA to fast neutrons and ␥-photons (12) and to prevent thermal denaturation of DNA (5). However, the protective effect of DNA-binding proteins cannot account for the extreme resistance of these microorganisms to heat and ␥-irradiation (12,14,20), suggesting the presence of very active mechanisms for DNA repair.Among the lesions induced by ionizing radiation in cellular DNA, double-strand breaks (DSBs) are the least efficiently repaired, and their frequency is correlated with cell death (9). Indeed, E. coli and most other organisms cannot survive if more than two or three DSBs are introduced per chromosome, independently of their physiological state (15,21).…”
mentioning
confidence: 99%
“…Thermophilic members of the Archaea have histone proteins (24) known to give partial protection of plasmid DNA to fast neutrons and ␥-photons (12) and to prevent thermal denaturation of DNA (5). However, the protective effect of DNA-binding proteins cannot account for the extreme resistance of these microorganisms to heat and ␥-irradiation (12,14,20), suggesting the presence of very active mechanisms for DNA repair.…”
mentioning
confidence: 99%
“…In both cases the amount of free linear duplex decreases faster than that of free bulged DNA. Clearly the affinity of MC1 decreases with the number of extra bases [linear duplex Ͼ (A) 2 Ͼ (A) 4 Ͼ (A) 6 ], and bulged DNA with six adenines is a poor ligand for MC1.…”
Section: Chemical Footprintings Of a Mc1−four-way-junction Complexmentioning
confidence: 99%
“…It protects DNA against thermal denaturation [5] and against radiolysis by fast neutrons [6]. Previous studies have shown that MC1 binding induces bends in DNA.…”
mentioning
confidence: 99%